Study on the selective laser sintering of a low-isotacticity polypropylene powder. Issue 4 (20th June 2016) - Zhu, Wei; Yan, Chunze; Shi, Yunsong; Wen, Shifeng; Han, Changjun; Cai, Chao; Liu, Jie; Shi, Yusheng
Abstract : Purpose: Semi-crystalline polymers such as polyamide-12 can be used for selective laser sintering (SLS) to make near-fully dense plastic parts. At present, however, the types of semi-crystalline polymers suitable for SLS are critically limited. Therefore, the purpose of this paper is to investigate the processibility of a new kind of semi-crystalline polypropylene (PP) with low isotacticity for SLS process. Design/methodology/approach: The SLS processibility of the PP powder, including particle size and shape, sintering window, degree of crystallinity and degradation temperature, was evaluated. Effects of the applied laser energy density on the surface micromorphology, density, tensile strength and thermal properties of SLS-built PP specimens were studied. Findings: The results show that the PP powder has a nearly spherical shape, smooth surfaces, an appropriate average particle size of 63.6 μm, a broad sintering window of 21 oC and low crystalline degree of 30.4 per cent comparable to that of polyamide-12, a high degradation temperature of 381.8°C and low part bed temperature of 105°C, indicating a very good SLS processibility. The density and the tensile strength first increase with increasing laser energy density until they reach the maximum values of 0.831 g/cm3 and 19.9 MPa, respectively, at the laser energy density of 0.0458 J/mm 2, and then decrease when the applied laser energy density continue to increase owing to the degradation of PP powders. The complex PP components have been manufactured by SLS using the optimum parameters, which are strong enough to be directly used as functional parts. Originality/value: This paper provides a new knowledge for this field that low-isotacticity PPs exhibit good SLS processibility, therefore increasing material types and broadening the application of SLS technology.